Impact and Beneficial Critical Points of Clinical Outcome in Corticosteroid Management of Adult Patients With Sepsis: Meta-Analysis and GRADE Assessment - Lin, Lu-Lu; Gu, Hui-Yun; Luo, Jie; Wang, Long; Zhang, Chao; Niu, Yu-Ming; Zuo, Hong-Xia (Frontiers in Pharmacology, 2019)
BACKGROUND: With new randomised pieces of evidence and the latest clinical practice guideline from the BMJ emerging in 2018, an updated analysis of best available evidence on the controversial effects of corticosteroids in sepsis is warranted. OBJECTIVES: To comprehensively evaluate whether corticosteroids are beneficial in reducing mortality and what cumulative dosage, daily dosage, and duration of corticosteroid treatment would enable adult patients with sepsis to reach the critical point of benefits. METHODS: Ovid MEDLINE, Ovid EMbase, Cochrane Library, and LILACS database were searched until March 22, 2019. RESULTS: 30 RCTs with 8,836 participants were identified. Long course low-dose corticosteroid therapy could improve 28-day mortality (RR=0.90, 95%CI=0.84–0.97; high quality), intensive care unit mortality (RR=0.87; 95%CI=0.79–0.95; moderate quality), and in-hospital mortality (RR=0.88, 95%CI=0.79–0.997; high quality). However, we found no benefits for 90-day, 180-day, and 1-year mortality. Subgroup results of long course corticosteroid treatment in a population with septic shock and vasopressor-dependent septic shock, corticosteroid regimen with hydrocortisone plus fludrocortisone, corticosteroid dosing strategies including bolus dosing and infusion dosing, the strategies of abrupt discontinuation, timing of randomisation ≤24 h, impact factor of ≥10, and sample size ≥500 were associated with a marginally reduction in 28-day mortality. CONCLUSIONS: This meta-analysis found that the long course low-dose and not short course high-dose corticosteroid treatment could marginally improve short-term 28-day mortality with high quality, especially septic shock and vasopressor-dependent septic shock, and it is recommended that long course (about 7 days) low-dose (about 200–300mg per day) hydrocortisone (or equivalent) with cumulative dose (at least about 1,000mg) may be a viable management option for overall patients with sepsis, and it can be also adapted to patient with septic shock alone. Early hydrocortisone plus fludrocortisone administration, via continuous infusion or bolus dosing, is also particularly important for the prognosis. Abrupt discontinuation of corticosteroids, as opposed to the conventional tapered discontinuation, may be considered as a desirable option in 28-day mortality. The safety profile of long course low-dose corticosteroid treatment, including adverse hyperglycaemia and hypernatraemia events, remains a concern although these events could be easily treated. TRIAL REGISTRATION: PROSPERO, CRD 42018092849.